2020
DOI: 10.3389/fpsyt.2020.00431
|View full text |Cite
|
Sign up to set email alerts
|

State-Independent Microstructural White Matter Abnormalities in Major Depressive Disorder

Abstract: Background: Even with continuous antidepressant treatment, residual symptoms and the risk of relapse can persist in remitted major depressive disorder (MDD) patients. Hence, having a clear recognition of the persistent abnormalities of the underlying neural substrate in MDD through a longitudinal investigation is of great importance.Methods: A total of 127 adult medication-free MDD patients with an acute depressive episode and 118 matched healthy controls (HCs) underwent diffusion tensor imaging. Over a 6-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…SC reduction of the insula in acute MDD, even in remitted MDD, had been reported in previous studies (3)(4)(5)(6). Also, FA reduction in insula has been reported in our earlier study in patients with MDD from the acute episode to remission and was regarded as a state-independent character (33). In the present study, we found that decreased SC of the insula retained from the episode phrase to the remission in MDD patients after 6-month treatment, which provides ampler evidence for the state-independent character of insula.…”
Section: Discussionsupporting
confidence: 74%
“…SC reduction of the insula in acute MDD, even in remitted MDD, had been reported in previous studies (3)(4)(5)(6). Also, FA reduction in insula has been reported in our earlier study in patients with MDD from the acute episode to remission and was regarded as a state-independent character (33). In the present study, we found that decreased SC of the insula retained from the episode phrase to the remission in MDD patients after 6-month treatment, which provides ampler evidence for the state-independent character of insula.…”
Section: Discussionsupporting
confidence: 74%
“…No changes in SC were observed after the treatment. Dong et al [ 34 ] 62 MDD, 118 HC -SSRIs or SNRIs -6 months -FA -MRI before and after treatment Decreased FA in the left insula, left middle occipital gyrus, right thalamus, left pallidum, and left PCu were observed in MDD compared with HC. No significant change in FA was observed after the treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Davis et al (2019) and Dong et al (2020) investigated the effect of SSRIs and SNRIs on SC but found no significant changes after 8 weeks, and 6 months after treatment, respectively [ 32 , 34 ]. Fan et al (2020) found four SC alterations in patients with MDD compared to HC.…”
Section: Resultsmentioning
confidence: 99%
“…Beside SSRIs and SNRIs, Hoogenboom et al ( 32 ) investigated the combined effects of several antidepressants, including norepinephrine and dopamine reuptake inhibitors, tricyclic antidepressants, lithium, noradrenergic and specific serotonergic antidepressants, serotonin antagonist and reuptake inhibitors. The majority of the studies adopted a pharmacological treatment lasting in total between 8 and 12 weeks, except for three studies that considered either a more extended (24 weeks and 12 months) ( 31 , 32 ) or shorter (2 days) ( 35 ) temporal window. Out of ten studies, only four investigated MD, AD and RD other than FA ( 30 , 34 , 35 , 38 ).…”
Section: Resultsmentioning
confidence: 99%